AN INSIGHT INTO OPHTHALMIC DRUG DELIVERY SYSTEM (International Journal of Pharmaceutical Sciences and Drug Research, 2009)
Promising management of eye ailments take off effective concentration of drug at the eye for sufficient period of time. Dosage forms are administered directly to eye for localized ophthalmic therapy. Most of the treatments call for the topical administration of ophthalmic active drugs to the tissues around the ocular cavity. Conventional ophthalmic drug delivery systems including eye drops, ophthalmic ointments, are no longer sufficient to encounter eye diseases. This article reviews the constraints with conventional ocular therapy and explores various novel approaches like in-situ gel, ocular films or ocuserts, nanosuspension, collagen shields, latex systems, nanoparticles, liposomes, niosomes, iontophorosis, eye implants, etc to improve the ophthalmic bioavailability of drugs to the anterior chamber of the eye.